2018
DOI: 10.4171/jst/252
|View full text |Cite
|
Sign up to set email alerts
|

Level repulsion for Schrödinger operators with singular continuous spectrum

Abstract: We describe a family of half-line continuum Schrödinger operators with purely singular continuous spectrum on (0, ∞), exhibiting asymptotic strong level repulsion (known as clock behavior). This follows from the convergence of the renormalized continuum Christoffel-Darboux kernel to the sine kernel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For one-dimensional continuum decaying model, Nakano [5] showed that the statistics for α > 1 2 is clock and for α = 1 2 , it is circular β-ensemble, see also Kotani [38]. Avila-Last-Simon [34] showed quasi-clock behaviour for ergodic Jacobi operator in region of absolutely continuous spectrum and Breuer-Weissman [8] showed the strong level repulsion (uniform clock behaviour) for one dimensional continuum model with purely singular continuous spectrum.…”
Section: Now We Consider the Rescale Matrixmentioning
confidence: 99%
“…For one-dimensional continuum decaying model, Nakano [5] showed that the statistics for α > 1 2 is clock and for α = 1 2 , it is circular β-ensemble, see also Kotani [38]. Avila-Last-Simon [34] showed quasi-clock behaviour for ergodic Jacobi operator in region of absolutely continuous spectrum and Breuer-Weissman [8] showed the strong level repulsion (uniform clock behaviour) for one dimensional continuum model with purely singular continuous spectrum.…”
Section: Now We Consider the Rescale Matrixmentioning
confidence: 99%
“…In light of the above results and discussion, it is natural to wonder whether singularity of µ implies less regularity of the asymptotic zero spacing. The example in [2] (see [3] for a continuum Schrödinger operator analog) shows that the situation in the case of R is more subtle. By considering the Jacobi coefficients associated with µ on R, [2] presents a family of purely singular measures where bulk universality, and therefore clock behavior, holds at every point of [−2, 2].…”
Section: Fix γ > 1 and Letmentioning
confidence: 99%
“…The observation is that the degree of continuity of the underlying measure, in terms of comparison with α-dimensional Hausdorff measure, implies a lower bound on the local spacing of the zeros. The second aim of this paper is to present the POPUC analog of an example on the real line [2,3] that shows that singular measures may still have strong asymptotic repulsion, implying that upper bounds coming from singularity of the measure are probably more subtle.…”
Section: Introductionmentioning
confidence: 99%